2016
DOI: 10.1371/journal.pone.0161075
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Higher Order Aberrations in Granular, Lattice and Macular Corneal Dystrophies

Abstract: PurposeTo evaluate the corneal higher-order aberrations (HOAs) in granular, lattice and macular corneal dystrophies.MethodsThis retrospective study includes consecutive patients who were diagnosed as granular corneal dystrophy type2 (GCD2; 121 eyes), lattice corneal dystrophies type 1, type 3A (LCDI; 20 eyes, LCDIIIA; 32 eyes) and macular corneal dystrophies (MCD; 13 eyes), and 18 healthy control eyes. Corneal HOAs were calculated using anterior segment optical coherence tomography, and the correlations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 31 publications
(33 reference statements)
4
40
0
Order By: Relevance
“…HOA was defined as the root mean square (RMS) of the 3rd to 8th order Zernike coefficients as a previous report. [ 15 ] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HOA was defined as the root mean square (RMS) of the 3rd to 8th order Zernike coefficients as a previous report. [ 15 ] …”
Section: Methodsmentioning
confidence: 99%
“…Wavefront analyses to quantify lower-order aberrations and HOAs have explained the decreased visual acuity and contrast sensitivity in normal eyes [ 10 ] and in eyes with a number of disorders. [ 11 14 ] Our group has recently demonstrated elevated HOAs of the posterior cornea caused by an irregular surface in various diseases of the corneal surface[ 15 18 ] and found a significant correlation between corneal HOAs and visual acuity in patients.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of irregular astigmatism is not limited to the superficial corneal dystrophies. Yagi-Yaguchi et al reported the results of corneal higher-order aberration measurements in patients with GCD, LCD, and MCD [34]. The authors found that patients with LCD and MCD in particular had topographies indicative of irregular astigmatism; as we mentioned earlier, this may be related to prior RCEs with subsequent epithelial remodeling and/or advanced anterior stromal deposits with localized topographic changes.…”
Section: Irregular Astigmatismmentioning
confidence: 55%
“…Though we did not confirm the absence of higher order aberrations (HOAs) in this patient, but their effect in patients with corneal dystrophies is known to cause visual distortions. 8 High modulus soft contact lenses may also be tried though their ability to mask surface irregularities is not as good as RGPs. 9 The goal of CL fitting in cases of corneal dystrophies is to reduce the visual symptoms without causing any harm to the cornea, hence an apical clearance RGP fit is preferred (fitting steeper than the flat keratometry reading) which allows for some tear exchange while preventing mechanical insult from the lens to the irregular central cornea.…”
Section: Discussionmentioning
confidence: 99%